Perancangan Protocol TCP/IP pada Jaringan Topologi Star dengan Metode Experimen pada Cisco Packet Tracer Versi 8.2.2 - Ira Zulfa; Rahmadi Asri; Kurnia Azmi (Prosiding Seminar Nasional Ilmu Teknik, 2026)
This research discusses the design, implementation, and performance analysis of the TCP/IP protocol on a star topology network using Cisco Packet Tracer version 8.2.2. The study aims to evaluate network communication effectiveness and demonstrate the advantages of star topology in improving stability, scalability, management efficiency, and data transmission performance compared to the previously implemented bus topology at the Faculty of Engineering Laboratory, Gajah Putih University. The research method used is a simulation-based experimental approach by designing and configuring a virtual network environment consisting of personal computers, laptops, servers, and network switches. The testing process focuses on host-to-host communication, packet transmission, connectivity analysis, delay measurement, and packet loss evaluation. The simulation results indicate that the TCP/IP protocol operates effectively within the star topology network, providing reliable communication with minimal packet loss and acceptable delay performance. Furthermore, the star topology demonstrates better network organization by reducing the possibility of data collisions, improving fault isolation, and simplifying troubleshooting processes. The findings indicate that the integration of TCP/IP protocols with a star topology architecture provides a more efficient and reliable network solution for educational laboratory environments. Therefore, this implementation can be considered a practical approach for improving network performance, supporting learning activities, and preparing infrastructure for future network development.